The Relationship between Physical Activity and Social Interaction of Elementary School Students - Sindy Oktaviani; Tatang Muchtar Tatang; Dewi Susilawati Dewi (UNIB Press, 2024)
This research aims to investigate the relationship between physical activity and social interaction using quantitative descriptive methods and correlational research designs. Social interactions play an important role in students' social development, and physical activity may influence this aspect. Data was collected by distributing assessment questionnaires to 31 samples who were students in grades 4 and 5 of SD Negeri Cikadu. This research aims to understand whether there is a correlation between physical activity and the development of students' social interactions. The research results show that there is a correlation between physical activity and verbal interaction of 0.522 which is included in the sufficient category. Then there is a correlation between physical activity and physical interaction of 0.371 which is included in the weak category. Furthermore, the relationship between physical vitality and emotional interaction shows a figure of 0.440 which is included in the sufficient category.